Marketing Strategy Analysis to Increase Sales of Ice Cream Bowls in Surabaya - Damis Veri Budianto; Imam Mukhlis; Arief Noviarakhman Zagladi (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to analyse marketing strategies for the sustainability of the Ice Cream Bowl Surabaya business. This research is a qualitative research. The main source of research data is the owner of Ice Cream Bowl Surabaya (Owner). While the research method is to conduct direct observation or observation techniques and in-depth interviews. The informants in this interview were 2 people, namely the owner as the main director and director. The conclusions are: 1) Ice Cream Bowl Surabaya sells its products through e-commerce; 2) Ice Cream Bowl Surabaya diversifies its products by developing product lines